Analysis of TAF90 Mutants Displaying Allele-Specific and Broad Defects in Transcription - Durso, Robert J. (American Society for Microbiology, 2001)
Yeast TAF90p is a component of at least two transcription regulatory complexes, the general transcription factor TFIID and the Spt-Ada-Gcn5 histone acetyltransferase complex (SAGA). Broad transcription defects have been observed in mutants of other TAF(II)s shared by TFIID and SAGA but not in the only two TAF90 mutants isolated to date. Given that the numbers of mutants analyzed thus far are small, we isolated and characterized 11 temperature-sensitive mutants of TAF90 and analyzed their effects on transcription and integrity of the TFIID and SAGA complexes. We found that the mutants displayed a variety of allele-specific defects in their ability to support transcription and maintain the structure of the TFIID and SAGA complexes. Sequencing of the alleles revealed that all have mutations corresponding to the C terminus of the protein, with most clustering within the conserved WD40 repeats; thus, the C terminus of TAF90p is required for its incorporation into TFIID and function in SAGA. Significantly, inactivation of one allele, taf90-20, caused the dramatic reduction in the levels of total mRNA and most specific transcripts analyzed. Analysis of the structure and/or activity of both TAF90p-containing complexes revealed that this allele is the most disruptive of all. Our analysis defines the requirement for the WD40 repeats in preserving TFIID and SAGA function, demonstrates that the defects associated with distinct mutations in TAF90 vary considerably, and indicates that TAF90 can be classified as a gene required for the transcription of a large number of genes.